Morphological descriptive study of giardia lamblia in man and cow at basrah - Al-Saad, Rasha; Al-Emarah, Ghazi (International Journal of Biological Research, 2014)
Giardia was single celled microscopic protozoan parasites that cause enteric disease in human. Because of the impact on socio-economic development, especially in developing countries, it was included in the “Neglected Disease Initiative” of the World Health Organization. This work conducted to descript morphology of Giardia spp in different hosts, which is first study of its type in Basrah, Iraq. This work started from September 2012 till June 2013, through this period collected 2393 stool samples from human and cows. 727 out of 2393 were positive. By using golden standard microscopic methods for diagnosis. A selective 30 positive stool samples for each hosts, measured the dimensions of stages of Giardia.  There is different measurement in dimensions of both two phases of Giardia. Keywords: Giardia Lamblia, Trophozoite, Cyst, Lugol?s Iodine, Giemsa.